On the Cauchy Problem for a Class of Semilinear Hyperbolic Equations with Discontinuous Coefficients and Data (Journal of Partial Differential Equations, 1996)
ln this paper we establish the existence of local solution to the Cauchy problem for a class of semilinear second order hyperbolic equations including degenerated type equations with discontinuous coefficients and data.